2006
DOI: 10.1364/oe.14.001862
|View full text |Cite
|
Sign up to set email alerts
|

Automatic characterization and segmentation of human skin using three-dimensional optical coherence tomography

Abstract: A set of fully automated algorithms that is specialized for analyzing a three-dimensional optical coherence tomography (OCT) volume of human skin is reported. The algorithm set first determines the skin surface of the OCT volume, and a depth-oriented algorithm provides the mean epidermal thickness, distribution map of the epidermis, and a segmented volume of the epidermis. Subsequently, an en face shadowgram is produced by an algorithm to visualize the infundibula in the skin with high contrast. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…The most successful application of OCT as optical diagnosis is in ophthalmology, where it can be used to create cross-sectional images of retinal pathology with higher resolution than any other noninvasive imaging technique, becoming the standard noncontact noninvasive ophthalmic imaging modalities for routine clinic diagnosis (8). Because of OCT potential to provide morphological information of biological tissues, it has been applied at other medical areas, such early diagnosis of ovarian neoplasia (9) and dermatology (10). Hard tissues like tooth were analyzed by OCT to verify the quality of dental restoration of enamel (11).…”
Section: Fracture Process Characterization Of Fiber-reinforced Dentalmentioning
confidence: 99%
“…The most successful application of OCT as optical diagnosis is in ophthalmology, where it can be used to create cross-sectional images of retinal pathology with higher resolution than any other noninvasive imaging technique, becoming the standard noncontact noninvasive ophthalmic imaging modalities for routine clinic diagnosis (8). Because of OCT potential to provide morphological information of biological tissues, it has been applied at other medical areas, such early diagnosis of ovarian neoplasia (9) and dermatology (10). Hard tissues like tooth were analyzed by OCT to verify the quality of dental restoration of enamel (11).…”
Section: Fracture Process Characterization Of Fiber-reinforced Dentalmentioning
confidence: 99%
“…OCT is now being increasingly employed in dermatology. 2 Previous studies have shown that the mean epidermal thickness (ET) obtained by OCT can be considered as a quantitative parameter for skin diagnosis 3 and quantitative treatment eÂźect assessment. 4,5 ET is also a good indicator of skin aging process.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain ET more rapidly and avoid user intervention, an automated algorithm is needed. In recent years, several automated methods have been reported to assess the ET by OCT, such as A-scan analysis, 3 shapelet analysis, 11 Markov chain 12 and active contour. 13 However, it is still unknown, about the eÂźectiveness of these algorithms when applied to clinical OCT images with artifacts or skin/hair debris.…”
Section: Introductionmentioning
confidence: 99%
“…Whether better results can be obtained by segmentation of single tissue layers, as presented by Hori et al [7], and allocation of different refractive indices may be addressed in future studies. …”
Section: Discussionmentioning
confidence: 97%